2020
DOI: 10.1111/jcmm.15661
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MALAT1 targeting STING transcription promotes bronchopulmonary dysplasia through regulation of CREB

Abstract: Bronchopulmonary dysplasia (BPD) is a severe complication of preterm infants characterized by increased alveolarization and inflammation. Premature exposure to hyperoxia is believed to be a key contributor to the pathogenesis of BPD. No effective preventive or therapeutic agents have been created. Stimulator of interferon gene (STING) is associated with inflammation and apoptosis in various lung diseases. Long non‐coding RNA MALAT1 has been reported to be involved in BPD. However, how MALAT1 regulates STING ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…Malat1 is ubiquitously expressed in all cells during early embryonic stages, while in adult tissues Malat1 expression varies among tissue types with high expression in the lung, brain, and pancreas [ 61 , 62 ]. Previous studies have shown that Malat1 expression is increased in peripheral blood samples from BPD patients and in rodent lungs of BPD models [ 63 , 64 ]. Malat1 was also increased in AT2 cells by neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Malat1 is ubiquitously expressed in all cells during early embryonic stages, while in adult tissues Malat1 expression varies among tissue types with high expression in the lung, brain, and pancreas [ 61 , 62 ]. Previous studies have shown that Malat1 expression is increased in peripheral blood samples from BPD patients and in rodent lungs of BPD models [ 63 , 64 ]. Malat1 was also increased in AT2 cells by neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are still contradictions regarding the detailed roles of certain lncRNAs. Some studies showed that lncRNA MALAT1 promoted BPD induced by hyperoxia through interacting with CREB 32 . However, other studies showed that lncRNA MALAT1 protected preterm infants with BPD by inhibiting cell apoptosis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…STING activation also plays a crucial role in bronchopulmonary dysplasia (BPD) in preterm infants (a lung inflammatory conditions induced due to hyperoxia) due to an increase in the long-non coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) that interacts with the cAMP response element-binding protein (CREB) to increase its transcription ( 128 ). MALAT1 increases HMGB1 concentration that may further activate cGAS-STING signaling by increasing the curvature of dsDNA that increases its binding potential to cGAS ( 129 ).…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%